2004
DOI: 10.1002/app.20639
|View full text |Cite
|
Sign up to set email alerts
|

Biaxially self‐reinforced high‐density polyethylene prepared by dynamic packing injection molding. II. Microstructure investigation

Abstract: Differential scanning calorimetry, wideangle X-ray diffraction, small-angle X-ray scattering, and transmission electron microscope are employed to study the microstructure of biaxially self-reinforced high-density polyethylene (HDPE) prepared in uniaxial oscillating stress field by dynamic packing injection molding. The results indicate that the biaxial self-reinforcement of HDPE is mainly due to the existence of interlocking shishkebab morphology (i.e., zip fastener structure), along with the orientation of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…Due to the features of sensitive response to shear flow and high flexibility in crystallization, for polyolefin chains both approaches of SCORIM and VAIM can efficiently produce shishkebab superstructure in the molded bars of single component polyolefin [90][91][92][93]. Although shear flow has been exerted on the melt via SCORIM approach, AFM micrographs acquired at different regions of the molded bar of polybutene-1, exhibited that interlocking shish-kebab morphology formed at the shear region whereas the crystals were isotropic spherulites in the core region [91].…”
Section: Shish-kebab Generated From the Single Component Melt Of Polymentioning
confidence: 99%
“…Due to the features of sensitive response to shear flow and high flexibility in crystallization, for polyolefin chains both approaches of SCORIM and VAIM can efficiently produce shishkebab superstructure in the molded bars of single component polyolefin [90][91][92][93]. Although shear flow has been exerted on the melt via SCORIM approach, AFM micrographs acquired at different regions of the molded bar of polybutene-1, exhibited that interlocking shish-kebab morphology formed at the shear region whereas the crystals were isotropic spherulites in the core region [91].…”
Section: Shish-kebab Generated From the Single Component Melt Of Polymentioning
confidence: 99%
“…From 2D‐WAXD and 1D‐WAXD patterns and results listed in Table , the intensity of diffraction peak (110) increased with mandrel rotation, implying the improved orientation of crystal plane (110) under circumferential stress . Furthermore, the average crystal size of the film at high mandrel speed was slightly larger than at low rotational speed.…”
Section: Resultsmentioning
confidence: 96%
“…Jun et al [7] used the DPIM device to prepare biaxially self-reinforced HDPE under the vibration in one direction, obtaining a 42% increase of the tensile strength in both MD and TD. The morphology [8] indicated that the biaxial self-reinforcement of HDPE was mainly due to the existence of an interlocking shish kebab morphology, along with the preferred orientation of the lamellae and the increased crystallinity.…”
Section: Introductionmentioning
confidence: 98%